2022
DOI: 10.30958/ajss.9-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAP) Towards COVID-19 among Older People Living in Informal Settlements in Nairobi City, Kenya

Abstract: Informal settlements in developing countries such as Kenya are the least prepared to deal with COVID-19 pandemic due to lack of basic housing, water and sanitation, and overcrowding. The risk is magnified for older people in such an environment due to their advanced age that compromises their immune system, and the fact that they are more likely to have pre-existing health conditions which weaken their body’s ability to fight infectious diseases. This study sought to establish older people’s knowledge levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, a significant number of respondents were aware that they were at risk of contracting COVID-19. Similarly, Kasozi et al ( 22 ) and Okaka and Omondi ( 23 ) reported that respondents were aware of the risk of contracting COVID-19 but the implementation of practices such as hand washing was problematic and challenging in Uganda and Kenya, respectively. This could be combated by investing heavily in the sensitization of the public to induce behavior change in communities, especially in future pandemics and epidemic outbreaks, such as the common Ebola and Marburg outbreaks, since adequate knowledge is often associated with good attitudes and practices ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a significant number of respondents were aware that they were at risk of contracting COVID-19. Similarly, Kasozi et al ( 22 ) and Okaka and Omondi ( 23 ) reported that respondents were aware of the risk of contracting COVID-19 but the implementation of practices such as hand washing was problematic and challenging in Uganda and Kenya, respectively. This could be combated by investing heavily in the sensitization of the public to induce behavior change in communities, especially in future pandemics and epidemic outbreaks, such as the common Ebola and Marburg outbreaks, since adequate knowledge is often associated with good attitudes and practices ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of literature, albeit confined to publications in Athens Journals, offers insights into numerous studies elucidating its impact on the economy and tourism industry[Adejare et al (2022),Jones (2022),Jones and Comfort (2020),Reid (2022),Tran (2023)], the Management/ Finance[Gukiina and Lamunu (2021),Struwig and Watson (2023),Uwah et al (2022)]. Health[Crescentini and Padricelli (2023),Galea (2022),Menekli et al (2021),Mukherjee and Ray (2023),Shah et al (2022),Stoyanov (2023),Uysal et al (2020), ŽegaracLeskovar et al (2022)], Social/ Media/Sports[Bäckman (2021), Cezar Dias and Moreira de Oliveira (2023), De Falco (2021),Fitzpatrick (2022),Jurić (2022a, b),Lust (2022),Mengu et al (2021),Okaka and Omondi (2022),Osisanwo (2022), Polo Martín (2022), Regret Iyer (2023,Stefani (2023)], Education[Charalambous and Papademetriou (forthcoming),Güvercin et al (2022), Jereb et al (2023,Makgopa (2022), Oluwadamilola Uleanya and Mulliah Naidoo (2023), RodariMeisner and McKenzie (2023), Turan-Güntepe et al (2023)], Technology[Hassan and Bellos (2022),Ismaili and Ibrahimi (2021),Joolfoo and Hosany (2023)], and Law/Judiciary[Iancu (2023[Iancu ( , 2021,Patraus and Ofrim (2021)].…”
mentioning
confidence: 99%